Designing of Anti keratin Antibody kit by Immuno fluorescent assay (IFA) and it's evaluation in Rheumatoid Arthritis (RA) pathients - F. Abedian; H, Baradaran; M. Saghafi; S.A. Rezaee; S.R. Mazloom; Z. Abedian (Journal of Mazandaran University of Medical Sciences, 2005)
Background and purpose: Rheumatoid Arthritis (RA) is a systemic auto immune Rheumatoid diseases. Auto antibodies are detected in this disease, with diagnostic and prognostic properties. One of them is AKA which reacts with the fibrous keratin in epiderm and the stratum corneum of rat esophageal epithelium. Hence at first AKA – IFA kit was designed, then its sensitivety and specificity was measured, and the titer of Anti body was evaluated in RA patients, and finaly the results of AKA were compared with that of RF test.Materials and method: AKA-IFA kit was designed with protein antigens in the stratum corneum of rat esophageal and anti human IgG conjugated to FITC.52 patients with RA (mean age 48.0 ±15.8) according to the American College of Rheumatology (ACR) criteria were selected for measuring the sensitivity and specificity. The results of AKA test in sera of RA patients were campared with 23 sera of patient control groupe (mean age 32.5 ±16.4) and 30 sera of healthy control groupe (mean age 32.1 ±16.9). Inter and intra assay method was used to determinig precision of AKA kit. RF test was also performed and it's results compared with result of designed AKA kit.Results: AKA were found in 75% of patients with RA (39/52), 13% of patient control groupe (3/23) and 3.3% of healthy control groupe .(YBO)The designed AKA kit by inter and intra assay method had 100% and 98% percision respectively. The sensitiviety and specificity of AKA in (1/10) serum dilution was 75% and 92.5% respectively but sensitiviety and specificity of RF was 88.5% , 86.8% respectively. Conclusion: According to the results, IFA– AKA test could be diagnostic and confirmative for RA , And AKA in (1/10)serum dilution has the best diagnostic Value for RA. (cut off).